Dramatic enhancement of double-walled carbon nanotube quality through a one-pot tunable purification method. (December 2016) - Desforges, Alexandre; Bridi, Angélica Vieira; Kadok, Joris; Flahaut, Emmanuel; Le Normand, François; Gleize, Jérôme; Bellouard, Christine; Ghanbaja, Jaafar; Vigolo, Brigitte
Abstract: The purification process we propose is a one-pot gas-phase treatment; the CNT powder is simply submitted to a chlorine/oxygen atmosphere at around 1000 °C for 2 h. By varying the oxygen content in an excess of chlorine, the conditions were optimized in order to efficiently remove both metal (catalyst) and carbon impurities from DWCNT samples. Even if a high amount of sample is lost under the oxidative conditions used, a selective elimination of the carbon impurities obviously occurs and a metal impurity removal yield of 99% is obtained from thermogravimetry. Based on a multi-technique approach, we show that the purified DWCNTs are of high structural quality without any surface functionalization. This improvement of the wall quality through the chlorine/oxygen action is seen in particular with a division by 15 of the D over G band intensity of the Raman spectra. Among the existing procedures, the advantages of our purification method are indisputably its simplicity, low time-consuming and high efficiency combined with an enhanced quality of the purified CNTs. Such quasi-pure DWCNTs have high interest since they offer a unique opportunity to study the intrinsic properties and effects of the nanotubes themselves.